Epidemiology of viruses causing chronic hepatitis among populations from the Amazon Basin and related ecosystems Epidemiología de las hepatitis crónicas con carácter vírico en las comunidades indígenas de la cuenca amazónica y de otros ecosistemas similares - José M. Echevarría; Pilar León (Cadernos de Saúde Pública, 2003)
On the last twenty years, viral hepatitis has emerged as a serious problem in almost all the Amerindian communities studied in the Amazon Basin and in other Amazon-related ecological systems from the North and Center of South America. Studies performed on communities from Bolivia, Brazil, Colombia, Peru and Venezuela have shown a high endemicity of the hepatitis B virus (HBV) infection all over the region, which is frequently associated to a high prevalence of infection by hepatitis D virus among the chronic HBV carriers. Circulation of both agents responds mainly to horizontal virus transmission during childhood through mechanisms that are not fully understood. By contrast, infection by hepatitis C virus (HCV), which is present in all the urban areas of South America, is still very uncommon among them. At the moment, there is not data enough to evaluate properly the true incidence that such endemicity may have on the health of the populations affected. Since viral transmission might be operated by mechanisms that could not be acting in other areas of the World, it seems essential to investigate such mechanisms and to prevent the introduction of HCV into these populations, which consequences for health could be very serious. A lo largo de los últimos veinte años, las hepatitis víricas se han revelado como un importante problema para las comunidades indígenas de la cuenca amazónica y de otros ecosistemas similares del norte y centro de Sudamérica. Los estudios realizados en comunidades de Bolivia, Brasil, Colombia, Perú y Venezuela han demostrado una alta propensión endémica para la infección por el virus de la hepatitis B, que se asocia con frecuencia a una elevada prevalencia de coinfección con el virus de la hepatitis D entre los portadores crónicos. La circulación de ambos agentes responde a su transmisión horizontal durante la infancia, a través de mecanismos aún poco conocidos. Por el contrario, la infección por el virus de la hepatitis C es aún muy infrecuente entre los indígenas. No existen, por el momento, datos suficientes para evaluar el impacto real que esta endemia pueda tener sobre la salud de esas poblaciones. Considerando que la transmisión de estos agentes podría involucrar mecanismos que quizá no actúen en otras regiones, parece indispensable investigar dichos mecanismos y prevenir cuidadosamente la introducción del virus de la hepatitis C en esas comunidades, ya que las consecuencias para su salud podrían ser muy graves.